2015
DOI: 10.1007/s00170-015-7155-6
|View full text |Cite
|
Sign up to set email alerts
|

Bionic design and verification of high-precision machine tool structures

Abstract: Highly stiff and lightweight machine tool structures are very important for improving machining accuracy. How to reasonably arrange stiffeners is one of the problems that designers must solve to achieve required structural performances. This paper presents a practical approach for stiffener layout design, which is inspired by the adaptive growth phenomenon observed in nature. Firstly, a mathematical model is built to provide theoretical basis for the adaptive growth of stiffeners to the applied load. Then a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Chen et al [6] put forward the feasibility of applying dynamic precision design (DAD) method to the design of super-precision fixture. Most of the other studies [7][8][9][10] propose to improve or develop similar methods for experimental analysis. However, in the process of ultra-precision machining, people often ignore the most basic and important component-chuck.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [6] put forward the feasibility of applying dynamic precision design (DAD) method to the design of super-precision fixture. Most of the other studies [7][8][9][10] propose to improve or develop similar methods for experimental analysis. However, in the process of ultra-precision machining, people often ignore the most basic and important component-chuck.…”
Section: Introductionmentioning
confidence: 99%
“…25 Based on the adaptive growth phenomenon in nature, Yan et al. 26 presented a practical method to optimize the design of stiffener layout, and developed the corresponding algorithm to realize the formation of stiffener layout. Wu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that bionic design not only could improve the overall mechanical properties of digging shovel, but also could help to improve the harvesting effect of cassava harvester. A mathematical model was established to provide theoretical basis for the adaptive growth of stiffeners to the applied load by Yan et al., 21 and a corresponding algorithm was developed to realize the generation of stiffener layout.…”
Section: Introductionmentioning
confidence: 99%